Greenland root phenology: warming and herbivory - David Eissenstat (Arctic Data Center, 2016)
Data on root and shoot phenology. Plots were were warmed with open top chambers and herbivores were excluded in a fully factorial design. This data was used in the publication of L. Radville, D.M. Eissenstat, and E. Post, Climate Change Responses 2016.